1949
DOI: 10.1103/physrev.75.555
|View full text |Cite
|
Sign up to set email alerts
|

Neutron-Proton Scattering at 90 Mev

Abstract: This document is reproduced as a project report and is without editorial preparation. The manuscript has

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

1950
1950
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…For simplicity~ the Be7 production rate was computed with no decay corrections (before end of bombardment) 9 since the error involved was negligible in 13 hours -40-intermittent bombardmento Using the ell beta .transzds.sion data from The cloud .chamber used was of the rubber diaphragm type, with a diameter of 22 inches, and a depth of four incheso The chamber was placed horizontally in a ve_z. :tical magnetic field of 21 3 ~00 gauss produced by a peak current of 4ll000 amperes pulsed through a.---pair at;.…”
Section: Calculation Of J312 Cross Sectionmentioning
confidence: 99%
See 1 more Smart Citation
“…For simplicity~ the Be7 production rate was computed with no decay corrections (before end of bombardment) 9 since the error involved was negligible in 13 hours -40-intermittent bombardmento Using the ell beta .transzds.sion data from The cloud .chamber used was of the rubber diaphragm type, with a diameter of 22 inches, and a depth of four incheso The chamber was placed horizontally in a ve_z. :tical magnetic field of 21 3 ~00 gauss produced by a peak current of 4ll000 amperes pulsed through a.---pair at;.…”
Section: Calculation Of J312 Cross Sectionmentioning
confidence: 99%
“…-31-' S~me 'sample calculations will now be Jr esentedo Equation (9) was usuaitly modified"before actilal use in a calculation because the ~2 and ell co~ting rates were usually employed as follows g The Bl2…”
mentioning
confidence: 99%
“…The above results appear to have an important bearing on the theory of the meson, for it has been shown by Brueckner (1949) that the experimental curves for the distribution in angle and energy of the emitted mesons can be best accounted for in terms of a pseudo-scalar theory. I n contrast with the observations, scalar theory predicts a strong anisotropy in the angular distribution.…”
Section: (Iv) Experiments With Y-radiationmentioning
confidence: 84%
“…The events were measured on reprojection apparatus similar to that described by Brueckner et al 10 and shown in …”
Section: Reprojection and Recording Of Datamentioning
confidence: 99%